Analysis of Green Marketing Mix Factors On Hotel Industry (Study on Sintesa Peninsula Hotel Manado; Discovery Kartika Plaza Denpasar; Hyatt Regency Yogyakarta; Grand Melia Jakarta) - Lapian, Stanss Levynna Hermien Verronica Joyce; Tumbel, Altje (International Review of Management and Marketing, 2019)
The tourism and hotel sectors generally have the potential to have a negative impact on the environment, welfare and socio-culture of local communities, especially if the construction of these hotels does not follow the green building architecture. This study aims to identify and analyze the factors of green marketing mix in hospitality service industry using 7 P (Product, Price, Promotion, Place, Physical Evidence, Process and People) Concept. Based on various researches, the seven elements are adopted into green marketing concept known as Green 7P. This research uses Confirmation Factor Analysis method, which is a factor analysis technique where a priori based on known theory and concept, understood or determined previously developed a number of factors and variables with the aim to get new variable or factor representing some item or sub- variable, which is an observable variable. The results of factor analysis of 32 manifest variables (sub variables) measured resulted in 24 new indicators that can be used to observe and measure green marketing mix factors (green 7P), Green Product: 1) Recycled water; 2) Recycled paper; 3) Organic & non-organic waste bins; 4) Award (Award). Green Price: Competitive Tariff. Green Place: 1) Easy to reach; 2) Cleanliness; 3) Convenience. Green Promotion: 1) Environmental-themed ads; 2) Environmental programs involving the community. Green Physical Evidence: 1) Green building design; 2) Magnetic card key; 3) Water fixtures (water saving); 4) WWTP; 5) Automatic hand-dryer (electricity saving); 6) Green park. Green Process: 1) Energy-saving policy; 2) Centralized Electricity System; 3) There is Waste Treatment; 4) Paperless office; 5) 3R Policy (Reduce, Reuse, Recycle). Green People: 1) Guest participation on green behavior (not smoking in any place, saving electricity / water); 2) Hospitality of hotel employees; 3) Training. Keywords: green marketing; green marketing mix; hotel industry JEL Classification: M31 DOI: https://doi.org/10.32479/irmm.7116